The ten-day MBA a step-by-step guide to mastering the skills taught in America's top business schools - Silbiger, Steven (New York Harper Business, an Imprint of HarperCollinsPublishers, 2024)
"An updated and revised edition of The Ten- Day MBA, incorporating the latest theories and topics taught at America's top business schools"
Includes bibliographical references and index.
Keywords: Business; Management; Business education -- Curricula; Management -- Study and teaching; Master of business administration degree